Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.05.06.490876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urine-derived exosomes from individuals with IPF carry pro-fibrotic cargo

Abstract: Background: MicroRNAs (miRNA) and other components contained in extracellular vesicles may reflect the presence of a disease. Lung tissue, sputum and sera of individuals with idiopathic pulmonary fibrosis (IPF) show alterations in miRNA expression. We designed this study to test whether urine and/or tissue derived exosomal miRNAs from individuals with IPF carry cargo that can promote fibrosis. Methods: Exosomes were isolated from urine (U-IPFexo), lung tissue myofibroblasts (MF-IPFexo), serum from individuals … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Whether the level of vesicular SFRP1 correlates with fibrosis severity remains an open question which will be addressed in followup studies. In line, EVs were also found in urine of patients with IPF (Elliot et al, 2022). The authors reported a specific miRNA composition but little is known about the proteins transported by these vesicles.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Whether the level of vesicular SFRP1 correlates with fibrosis severity remains an open question which will be addressed in followup studies. In line, EVs were also found in urine of patients with IPF (Elliot et al, 2022). The authors reported a specific miRNA composition but little is known about the proteins transported by these vesicles.…”
Section: Discussionmentioning
confidence: 73%
“…We and others demonstrated the crucial role of EVs during pulmonary fibrosis (Martin-Medina et al, 2018; Njock et al, 2019; Parimon et al, 2019; Santos-Alvarez et al, 2022). These vesicles accumulate within the lungs of patients with IPF and can be collected in several body fluids such as BALF, sputum or urine (Elliot et al, 2022; Martin-Medina et al, 2018; Njock et al, 2019). During fibrosis, EVs exacerbate major mechanisms of disease such as proliferation and activation of fibroblasts (Elliot et al, 2022; Martin-Medina et al, 2018) or AT2 cells (Parimon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation